Counterproductive work behaviors and work climate: The role of an ethically focused management control system and peers' self-focused behavior. (January 2022) - Bellora-Bienengräber, Lucia; Radtke, Robin R.; Widener, Sally K.
Abstract: The importance of curtailing undesirable behaviors and, ultimately, self-focused work climates in organizations is undeniable. This study examines how management control systems (MCSs), as a crucial part of a firm's formal ethical infrastructure, can contribute to this objective. We conceptualize an ethically focused MCS as one that communicates ethical values and motivates employees to act accordingly. Our study is based on data from a sample of 120 department managers from 120 different firms. We show that department managers' perceptions of the extent to which the MCS imposed on them is ethically focused are associated with a reduction in their counterproductive work behaviors (CWBs). We also examine department managers' perceptions of peer managers' self-focused behaviors, as a core part of a firm's informal ethical infrastructure and find that peers' behaviors are not associated with an increase in CWBs of the department manager. However, we find some evidence that the negative association between an ethically focused MCS and managers' CWBs is limited when peers act in ways that are more self-focused. Finally, we find that CWBs of department managers are not only relevant in and of themselves, but they translate into more self-focused behaviors of department employees (as manifested in their work climates). Overall, this study suggests that, while including and emphasizing ethical content in the MCS is associated with less CWB and, in turn, with a work climate less focused on self, peer managers' behaviors are also seemingly important.